Active roll control strategy using fuzzy logic control active suspension - Phuman Singh, A.S.; Mat Darus, I.Z. (WSEAS Journals, 2014)
An active roll control system using a combination of feedback and feedforward fuzzy logic control active suspension for enhancement of vehicle roll dynamics is presented in this paper. The dynamics model representing the vehicle behavior was first developed and then modeled in the Matlab/SIMULINK environment. The tire model used was developed based on tire test data using loop up table method. The validity of the vehicle model was verified using CarSim software for double lane change maneuver. The inputs to the feedforward fuzzy logic control were the driver steering wheel angle and vehicle longitudinal velocity and the output of the feedforward fuzzy logic control was the counter roll moment. For the feedback fuzzy logic control, the roll angle error and error rate were the inputs whereas the counter roll moment was the output. The effectiveness of the proposed control system was demonstrated for fishhook, step steer, and double lane change maneuvers and this vehicle roll control system has shown its capability in reducing vehicle rollover propensity.